(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The research identifies the challenges faced for the implementation and usage of the production control systems. Some challenges like high level of investment and maintenance, negative feedback from employees, deviation system, rules and regulations of government, unforeseen emergencies are taken for the evaluation. The intensity of these challenges for the production control in large scale industries is identified. The research gives the idea about the benefits of the production control practices. Production control avoids the deviations and interruption of the production lines. Production control practices improves the overall performance of the production system which includes improvement in purchase management, production technology, wastage management, customer service and cost saving.